New insights into the photoswitching mechanisms of normal dithienylethenes. Issue 40 (3rd October 2016) - Hamdi, I.; Buntinx, G.; Perrier, A.; Devos, O.; Jaïdane, N.; Delbaere, S.; Tiwari, A. K.; Dubois, J.; Takeshita, M.; Wada, Y.; Aloïse, S.
Abstract : The photoswitching of photochromic diarylethene and bridged analog have been investigated by TD-DFT, ultrafast spectroscopy and chemometric data treatments. New photochemical pathways and individual spectral signatures have been determined. Abstract : The photoswitching and competitive processes of the referent photochromic diarylethene derivative 1, 2-bis(2, 4-dimethyl-5-phenyl-3-thienyl)perfluorocyclopentene (DTE) and a novel bridged analog DTE-m5 have been investigated by state-of-the-art TD-DFT calculations and ultrafast spectroscopy supported by advanced chemometric data treatments. Focusing on DTE, the overall deactivation pathway of both antiparallel (AP) and parallel (P) conformers of the open form (OF) (1 : 1 in solution) has been resolved and rationalized starting from the Franck–Condon (FC) region to the ground state recovery. For the photo-excited P conformer, after ultrafast relaxation (∼200 fs) towards the S1 relaxed state, an expected ISC occurred (55 ps) to produce a triplet state, 3 P, the latter relaxing within 2.5 μs. Concerning the AP conformer, the photocyclization reaction is reported to proceed immediately (100 fs) starting from the FC region while the relaxed singlet state is populated in parallel. For the first time, we discovered that the latter state evolves through an unexpected ISC process (1 ps) giving rise to a second triplet state, 3 AP. For DTE-m5, by slightly constraining the molecule with the bridge, this triplet becomes reactive and participates in the formation of 10% of closed form (CF) probably through an adiabatic mechanism. Concerning the photoreversion, in accordance with the literature, we report on a two-step process, a 190 fs vibrational relaxation followed by a 6 ps ring-opening reaction. For the overall species at the singlet or triplet manifold, the use of advanced MCR-ALS allows us to obtain specific spectral signatures. This study is therefore a new step within the comprehension of DTE photochemistry.